Self-Regulation of Social Exchange Processes in MAS: a cultural and evolutionary BDI agent society model - Laer, Andressa von; Dimuro, Graçaliz P.; Aguiar, Marilton S. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Agent interactions are often understood as service exchange processes between pairs of agents, followed by the evaluation of these services by the agents involved, generating social exchange values. For the social equilibrium of the agent society there should be an adequate balance of those values, which can be obtained by the regulation of the social exchange processes by the agents themselves. A hybrid evolutionary model of selfregulation of processes of social exchanges in MAS was proposed for Netlogo. However, certain characteristics involved in social exchanges are more appropriately dealt with BDI agents. This paper proposes to develop a model of agent society composed by cultural evolutionary BDI-like agents, for the self-regulation of processes of social exchanges, using the JaCaMo framework.